Bounded rationality in decision making: An analysis of the decision-making biases - Ana Rita Jord\~ao; Renato J. Lopes da Costa; Álvaro Lopes Dias; Leandro Pereira; José Pedro Santos (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Decision-making is a multidisciplinary and ubiquitous phenomenon in organizations, and it can be observed at the individual, group, and organizational levels. Decision making plays, however, an increasingly important role for the manager, whose cognitive competence is reflected in his ability to identify potential opportunities, to immediately detect and solve the problems he faces, and to predict and prevent future threats. Nevertheless, to what extent do managers of the most diverse sectors and industries continue to rely on false knowledge when they have better strategies at their disposal? The present article proposes, through the application of bibliographically based instruments, the diagnosis of three prominent biases - overconfidence, optimism, and anchoring effect - in managers of the Portuguese port sector, as well as also seeking to establish a comparative analysis with the conclusions already documented in relation to the Brazilian civil construction sector. In addition, and in view of the results obtained, this paper also provides a set of measures capable of contributing to the mitigation of the effects of these and other biases, and, in this way, to the improvement of the decisions of said managers.
Keywords: M12; M14; M54; 650; biases; overconfidence; optimism; anchoring effect; port sector